Networked mobbing in higher education institutions and its consequences on the wider academic community in Serbia - Maluckov, Biljana S. (Sociološki pregled, 2018)
The phenomenon that several people abuse one person both vertically and horizontally – a networked mobbing in the academic community, is a growing phenomenon in Serbia as a consequence of a difcult economic situation and a falling morale of the entire society. A networked mobbing is much more perfdious and much more severe than mobbing performed by one person. Mobbing has a negative impact on the victim’s quality of life and his/her family and can be lethal to the victim. The consequence of networked mobbing to the wider academic community is a negative selection of personnel, starting from the lowest level of the hierarchical scale of academic ranks, characterized by opportunistic-conformist behavior and a lack of integrity, and the fnal outcome of such selection is that professors do not voice out on the occasion of diploma purchases and plagiarism done by politicians. The paper presents proposals for combating the negative selection of personnel caused by mobbing.Keywords: mobbing, higher education institutions, suicide, plagiarism